2019
DOI: 10.5829/ije.2019.32.06c.06
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Mathematical Model for Designing an Organ Transplant Supply Chain Network under Uncertainty

Abstract: One of the most important issues in area of health and hygiene is location-allocation of organ harvesting centers and transplant centers according to coordination between supply and demand. In this paper, a mathematical model is presented for location-allocation of organ harvesting centers and transplant centers. The proposed model does not only minimize the present value of the total system costs, but also minimizes the geographical inequalities. The presented model is a bi-objective nonlinear mathematical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In addition, the findings emerging from this study have implications for the theory of constraints (Kim et al , 2008; Rahman, 1998; Simatupang et al , 2004), a technique used to determine the primary constraint to a system’s optimisation and then sequentially improving that constraint to the point where it is no longer the limiting factor. For instance, given that our research has used the STS theory to shed light on an inherent interaction between challenges in organ supply chains, the theory of constraints can facilitate identifying the most significant system constraints and prioritising resource allocation to effectively and efficiently provide critical transplant services to those in need.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, the findings emerging from this study have implications for the theory of constraints (Kim et al , 2008; Rahman, 1998; Simatupang et al , 2004), a technique used to determine the primary constraint to a system’s optimisation and then sequentially improving that constraint to the point where it is no longer the limiting factor. For instance, given that our research has used the STS theory to shed light on an inherent interaction between challenges in organ supply chains, the theory of constraints can facilitate identifying the most significant system constraints and prioritising resource allocation to effectively and efficiently provide critical transplant services to those in need.…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, few studies have demonstrated how supply chain management practices improve organ transplantation by focusing on time, geographical location and allocations (Cole, 2021;Aleccia, 2020). Others have developed models to minimise organ transport time (Beliën et al, 2011) and effectively match organ demand with supply (Rabbani and Talebi, 2019). However, due to their greater emphasis on developed nations, these studies demonstrate that our understanding of organ donation and transplant supply chain issues are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Charles et al (2019) formulated a probabilistic fuzzy SC network problem and solved it with three different approaches. Rabbani and Talebi (2019) proposed bi-objective nonlinear mathematical programming to minimize the present value of total system costs and the geographical inequalities in the location selection. Babbar and Amin (2018) proposed a mathematical model comprising a two-stage QFD and a stochastic multi-objective mathematical model to select suppliers and assign the order quantity.…”
Section: Fuzzy Operations Research Methods In Scmmentioning
confidence: 99%
“…Dey et al (2016) used a fuzzy decision making model to deal with the cross-docking location problem. Rabbani and Talebi (2019) established a mathematical model for locationallocation of organ harvesting centers and transplant centers. Zhao et al (2019) proposed an MCDM model considering cost, infrastructure, market, policy, technology and natural resources to solve a distribution center location problem.…”
Section: Applications Of Fuzzy Techniques In Scmmentioning
confidence: 99%
“…Health system management in the world involves different subjects such as supply chain management [42,43], data management [44,45,46], risk management [47], routing and scheduling management [48,49] and home healthcare management [50,51,52].…”
Section: Literature Reviewmentioning
confidence: 99%